Tripartite Entanglement in Quantum Memristors - Albarran-Arriagada, F (American Physical Society, 2022)
We study the entanglement and memristive properties of three coupled quantum memristors. We consider quantum memristors based on conductance-asymmetric superconducting quantum interference device architectures that are coupled via inductors. The three quantum memristors are arranged in two different geometries: linear and triangular coupling configurations. We obtain a variety of correlation measures, including bipartite entanglement and tripartite negativity. For identical quantum memristors, we find that entanglement and memristivity follow the same behavior for the triangular case and the opposite one in the linear case. Finally, we study the multipartite correlations with the tripartite negativity and entanglement monogamy relations, showing that our system has genuine tripartite entanglement. Our results show that quantum correlations in multipartite memristive systems have a nontrivial role and can be used to design quantum memristor arrays for quantum neural networks and neuromorphic quantum computing architectures. © 2022 American Physical Society.